(untitled) (Homoeopathy for All, 2023)
Chronic Kidney Disease (CKD) is a progressive and potentially debilitating condition that affects millions of people worldwide. It is characterized by the gradual loss of kidney function over an extended period, leading to the glomerular filtration rate (eGFR) and the presence of kidney damage. The eGFR measures how well the kidneys filter waste from the blood and is expressed in milliliters per minute per 1.73 square meters (m²) of body surface area. The stages are defined as follows: